APPROACH FOR ESTIMATING COHESION AND ANGLE OF INTERNAL FRICTION USING UNIAXIAL COMPRESSIVE AND TENSILE STRENGTH VALUES OF ROCKS - Melati, Sari; Hakim, Romla Noor; Santoso, Santoso; Arief, Muhammad Zaini (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
Rock characteristics, such as failure criteria, play a critical role in the assessment of stability in rock engineering, alongside design factors. Stability in rock engineering is cohesion (c) and friction angle (j) are parameters of failure criteria obtained by performing direct shear test or triaxial test. However, the measurements require a certain number of intact rock samples. On the restricted condition or preliminary study, an approach involves for predicting both parameters. Using data statistical analysis of Uniaxial Compressive Strength (sc) and Brazilian Tensile Strength (st) of limestone and gypsum, empirical equations to predict c dan j were resulted in this research. Cohesion is strongly determined by st with average constants in equations: c = 1.81st dan c = 1.84st, for limestone and gypsum. Cohesion of limestone depends on sc with average constant in equation: c = 0.22sc. Friction angle and rock strength ratio (sc/st) are related by exponential equations: c/st = 2.1624e0.0314j dan sc/st = 3.6936e0.0183j, for limestone and gypsum, respectively. This approach using constructed empirical equations provides the prediction of c and j that relevant with theoretical values, indicated by 2.8% and 8.22% relative deviations. These empirical equations are useful for predicting the values ​​of c and j.